PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA GURU SLB PADA YAYASAN PENDIDIKAN MANDIRI PUTRA LOWONG - Sari, Aisyah Arum; Tifani, Rona Netanya; Susdiyanto, Susdiyanto; Dasmadi, Dasmadi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to examine the role of human resource management at the Mandiri Pendidikan Putra Lowong Foundation. Data was obtained through a case study by directly observing the headmaster and teachers at the Special Education School of the Mandiri Pendidikan Putra Lowong Foundation. Training and development play a crucial role in improving the performance of the workforce in the education sector. This is important because the workforce may not be fully prepared for their tasks given the changing needs of society in the field of education. While administratively the workers may already meet the requirements, they still need to keep up with the relevant developments in education. The strategy for human resource development is primarily focused on enhancing skills, and participation in various training programs is mandatory. Furthermore, it is important to acknowledge that one training session is not sufficient. There are various types of training that can be undertaken to enhance skills and competencies. The results from the 2023 report indicate an improvement in the quality of teachers after participating in various training sessions and seminars. Overall, training and development of human resources play a crucial role in enhancing the quality of education and the performance of teachers. The results of this study indicate that human resource management has a positive partial effect on improving the skills of teachers at the Mandiri Pendidikan Putra Lowong Special Education School. With increased training and active participation in activities with students, teachers can more efficiently track the progress of their students and utilize their expertise more effectively.